2022
DOI: 10.3389/fgene.2022.827840
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Defined Super-Enhancer Associated Gene Signature to Predict Prognosis in Patients With Diffuse Large B-Cell Lymphoma

Abstract: Background: Diffuse large B-cell lymphoma (DLBCL) is a genetically heterogeneous disease that can have profound differences in survival outcomes. A variety of powerful prognostic factors and models have been constructed; however, the development of more accurate prognosis prediction and targeted treatment for DLBCL still faces challenges. An explosion of research on super-enhancer (SE)–associated genes provide the possibility to use in prognostication for cancer patients. Here, we aimed to establish a novel ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…PXK was significantly associated with the prognosis of diffuse large B cell lymphoma. 17 The G > T mutation in the “chr9:65675405-65675906” significantly increased the activity of the enhancer (log2FC = 2.51) in LumB subtype, which in turn was associated with the downregulation of potential target genes, such as CBWD5 and ANKRD20A3P ( Figure 3 C; Table S1 ). The C > T mutation in “chr22:36194883-36195384” had the significantly upregulated the enhancer activity in LumA subtype, which in turn was associated with the upregulation of target genes TXN2, APOL1, APOL2, APOL3, APOL4, and EIF3D ( Figure 3 D; Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…PXK was significantly associated with the prognosis of diffuse large B cell lymphoma. 17 The G > T mutation in the “chr9:65675405-65675906” significantly increased the activity of the enhancer (log2FC = 2.51) in LumB subtype, which in turn was associated with the downregulation of potential target genes, such as CBWD5 and ANKRD20A3P ( Figure 3 C; Table S1 ). The C > T mutation in “chr22:36194883-36195384” had the significantly upregulated the enhancer activity in LumA subtype, which in turn was associated with the upregulation of target genes TXN2, APOL1, APOL2, APOL3, APOL4, and EIF3D ( Figure 3 D; Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Oncogenic drivers known as super-enhancers, which are characterized by massive clusters of enhancers, have been shown to be crucial for maintaining cancer cell identity. It has been reported that SE significantly impacts the development of malignancies, and SE-related genes can serve as prognostic markers ( 7 , 8 , 12 , 13 ). However, no studies have demonstrated the correlations between the SE-related genes and prognosis in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SEs with broad and high H3K27ac signals have been identified in nasopharyngeal carcinoma and were found to be associated with overexpression of the ETV6 oncogene and poor prognosis 121 . Xu et al defined an SEassociated gene risk signature to predict the response to chemotherapy in patients with diffuse large B-cell lymphoma, which may help clinicians make more appropriate treatment decisions 122 . Moreover, in our previous studies, we constructed prognostic models based on SE-associated genes to predict overall survival for osteosarcoma and multiple myeloma patients, which may be helpful for clinical treatment 123,124 .…”
Section: Utility Of Ses In Tumor Prognosticationmentioning
confidence: 99%